Psychometric properties of the Arabic version of the McMaster family assessment device–general functioning subscale (FAD-GF) among a sample of Lebanese adults - Melyssa Assaf; Rabih Hallit; Diana Malaeb; Fouad Sakr; Mariam Dabbous; Feten Fekih-Romdhane; Sahar Obeid; Souheil Hallit (Cogent Psychology)
Background Family functioning is linked to physical and psychological health. The 12-item McMaster Family Assessment Device–General Functioning Subscale (FAD-GF) is used for assessing overall family functioning; however, it is not validated in Lebanon, a country undergoing socio-economic crises threatening family cohesion. Various factor structures for FAD-GF have been reported in prior studies, necessitating an evaluation of its applicability in the Lebanese context.Methods Four previously proposed models were tested. Model 1: the original one-factor 12-item structure (FAD-GF); Model 2: an abbreviated one-factor structure comprising the six positively worded items (FAD-GF6+); Model 3: An adapted two-factor structure with a positive 3-item factor and a negative 3-item factor; Model 4: a hypothetical three-factor structure including all 12 items.Results Models 2 and 3 had adequate fit based on confirmatory factor analysis. However, Model 3 showed suboptimal internal consistency (ω = 0.58, α = 0.67) and was not retained. Model 2 showed excellent internal consistency (ω = 0.90, α = 0.90), acceptable convergent validity (average variance extracted [AVE] = 0.61) and concurrent validity through significant negative correlations with intolerance of uncertainty, irritability, and aggression. Measurement invariance across genders was also confirmed.Conclusion The study provides preliminary evidence supporting the use of FAD-GF6+ as a reliable, valid, and context-appropriate tool for evaluating family functioning in the Arabic-speaking Lebanese population.